Analisis Pengaruh Penerimaan Pajak Daerah dan Retribusi Daerah terhadap Peningkatan Pendapatan Asli Daerah Kabupaten Brebes - Afti Sulastri; Maftukhin; Azizah Indriyani; Dumadi; Titi Rahmawati (Journal of Accounting and Finance (JACFIN), 2020)
This study aims to analyze the effect of local tax revenues and regional levies on local revenues in Brebes Regency. This study used 60 samples of reports on the realization of local taxes, regional levies and original regional income, each of which consisted of January-December 2015 - 2019 at the Brebes Regency BPPKAD agency. Samples were selected using the judgement sampling method. The data type used is secondary data. Data analysis using descriptive statistics, classical assumption testing, hypothesis testing and multiple regression analysis. The variables used in this study are local taxes and regional levies as independent variables, local original income as dependent variables. The results of this study showed that the results of the t test obtained t-count 18,437 > t-table 2,002 and Sig. 0.000 < 0.05 that partially the local tax had a significant effect on the original income of the area, the results of the t test were obtained t-count 3.058 > t-table 2.002 and Sig. t 0.003 < 0.05 that partially the regional levy had a significant effect on the original income of the county, and the test results of the F test, the F value calculated 414.542 > F table 3.16 and Sig. 0.000 < 0.05 that simultaneously the local tax and local levies have a significant effect on local revenues.